Forensic Accounting Skills and Auditor Self-Efficacy: Empirical Evidence From Indonesia - Firda Ayu Amalia; Khoirun Nisa' Syamsiyah; Dhaniel Syam (Accounting Study Program, Faculty Economics and Business, Universitas Sebelas Maret, 2024)
This study investigates the relationship between auditor self-efficacy and forensic accounting skills in detecting fraud. The data in this study are primary data with the sampling technique in this study using the purposive sampling method with the help of a questionnaire tool distributed to 138 auditors in Indonesia. The data analysis technique used in this study uses structural equality modeling (SEM) partial least squares (PLS) to test the hypothesis with the help of a tool in the form of Smart-PLS. The results of this study indicate that auditor self-efficacy is significantly correlated with technical and analytical skills, effective communication skills, psychosocial skills, accounting and audit skills. The originality of this study is to focus on forensic accounting skills in Indonesia and analyze how these skills improve Auditor Self-Efficacy (ASE) in detecting produces important information about auditor efficacy and competence.